Science and Technology Backyard: A novel approach to empower smallholder farmers for sustainable intensification of agriculture in China - Xiao-qiang JIAO; Hong-yan ZHANG; Wen-qi MA; Chong WANG; Xiao-lin LI; Fu-suo ZHANG (Journal of Integrative Agriculture)
Sustainable feeding of the growing population in China without ecological destabilization is a grand challenge. In this populous country where agriculture is dominated by smallholder farming, developing innovative technology and translating scientific knowledge into action for smallholder farmers is a crucial step in addressing this challenge. Here, we present a novel approach for technology innovation and dissemination to achieve sustainable intensification in the fields of smallholder farmers. The Science and Technology Backyard (STB) is a hub in a rural area that links knowledge with practices to promote technology innovation and exchange. In this study, the framework and functions of STB are introduced, and the key implications for sustainable intensification across millions of smallholder farmers are explicitly stated: (i) develop innovative technology based on stated demands of farmers; (ii) disseminate technology by innovative social service models though combined top-down approaches with bottom-up measures to enable smallholders in rural areas. This paper provides a perspective on transformation of small-scale agriculture toward sustainable intensification in China and useful knowledge applicable to other developing countries.